2019
DOI: 10.1039/c9cc02242b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free oxidative [2+2+1] heteroannulation of 1,7-enynes with thiocyanates toward thieno[3,4-c]quinolin-4(5H)-ones

Abstract: Transition-metal- and base-free oxidative [2+2+1] heteroannulation of 1,7-enynes with NaSCN as the sulphur source is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…In recent years, the free radical tandem bicyclization of 1, n -enynes has been developed rapidly . Much research has provided practical protocols for fascinating multiple bicyclization modes using active terminal 1,7-enynes, and radical bicyclizations are triggered by the β-position of α,β-unsaturated carbonyl compounds (Scheme a). , However, directly using inactive nonterminal 1, n -enynes as acceptors in the free radical tandem bicyclization remains challenging because of the large steric hindrance and poor selectivity when both CC and CC bonds are present. In 2015, the Tu group reported an appealing radical tandem bicyclization reaction triggered by the β-position of α,β-unsaturated ketones bearing nonterminal 1,5-enynes (Scheme b) . Most elegant free radical bicyclizations are triggered by the β-position of α,β-unsaturated carbonyl compounds, , while the α-position-triggered process has not yet been developed.…”
mentioning
confidence: 99%
“…In recent years, the free radical tandem bicyclization of 1, n -enynes has been developed rapidly . Much research has provided practical protocols for fascinating multiple bicyclization modes using active terminal 1,7-enynes, and radical bicyclizations are triggered by the β-position of α,β-unsaturated carbonyl compounds (Scheme a). , However, directly using inactive nonterminal 1, n -enynes as acceptors in the free radical tandem bicyclization remains challenging because of the large steric hindrance and poor selectivity when both CC and CC bonds are present. In 2015, the Tu group reported an appealing radical tandem bicyclization reaction triggered by the β-position of α,β-unsaturated ketones bearing nonterminal 1,5-enynes (Scheme b) . Most elegant free radical bicyclizations are triggered by the β-position of α,β-unsaturated carbonyl compounds, , while the α-position-triggered process has not yet been developed.…”
mentioning
confidence: 99%
“…Interestingly, all of them could give a certain yield, but they were inferior to the reaction in DMF (entries 16-22 vs entry 2). In addition, the further study found that the lower temperature (entries [23][24] or lower catalyst loading (entry 25) resulted in the diminishing yield of 3 aa, however, more catalyst loading (entry 26) didn't improve the yield of 3 aa as well. The results indicated that DTBP performed an important role in the reaction, because a lower loading of it leaded to the declining yield (entry 27) or the reaction was a failure at all (entry 28).…”
Section: Resultsmentioning
confidence: 93%
“…Recently, a radical‐mediated [2+2+n] strategy has proven to be powerful and efficient method for the construction of highly functionalized cyclic compounds from 1,n‐enynes, [16] in which, the [2+2+1] radical annulation showed terrific potential to synthesize fused ring compounds in a number of elegant studies (Scheme 1, Previous work). In these [2+2+1] radical annulation, oxidative cyclobutanone oximes, [17] 1,3‐dicarbonyl compounds, [18] 4‐methoxyanilines, [19] disulfides, [20] azidobenziodoxolone, [21] α ‐carbonyl alkyl bromides, [22] thiocyanates, [23] TMSN 3 , [24] DTBP, [25] alkyl nitriles or acetone, [26] α ‐bromo diethyl malonate, [27] alkylcarboxylic acids, [28] cycloalkanes, [29] and DCM [30] were usually driven as unary synthons. However, it could be inevitably found that all these reactions were almost invovled aniline‐linked 1,7‐enynes, while phenol‐linked 1,7‐enynes was very seldom used in this transformation due to their poor reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The Hao, Tu and Jiang group has reported a copper catalysis combined with the i Pr 2 NH base that enabled [2+2+1] heteroannulation of 1,6‐enynes with K 2 S leading to arylated indeno[1,2‐ c ]thiophenes (Scheme a). Very recently, we demonstrated a oxidative strategy for the [2+2+1] heteroannulation of 1,7‐enynes with NaSCN that serves as the sulfur atom source under transition‐metal‐ and base‐free conditions (Scheme b). In addition to the requirement of high loadings of Cu catalysts or excess amounts of oxidants, all of these syntheses rely strongly on the use of both a high temperature (120 °C) and an excess amount of sulfur‐containing metal salts that form undesired metal‐based byproducts, thereby compromising their synthetic applications .…”
Section: Methodsmentioning
confidence: 99%